Pengaruh Kualitas Pelayanan Terhadap Kepuasan Pengguna Jasa pada Marpoken Delivery Kecamatan Panyabungan Kabupaten Mandailing Natal - Nurhalisa Khairani; Rizka Ar Rahmah; Muhammad Ardiansyah (PPIMAN Pusat Publikasi Ilmu Manajemen, 2025)
This research aims to analyze the impact of service quality on customer saticfaction at Marpoken Delivery, Panyabungan District, Mandailing Natal Regency. With a population of service users from January to June 2024 and a sample size of 100 respondents, the study employs a quantitative research approach. Data were collected through observation, documentation, and questionaires, and then analyzed using SPSS version 29 with various statistical tests, including the t-test. The results indicate a calculated t-value of 10.903, exceeding the critical t-value of 1.661, with a significance level of 0.001 (less than 0.05). this demonstrates a positive and signivicant effect of service quality on customer satisfaction, with service quality contributing 54.8%, the remaining 45.2% of customer satisfaction is influenced by other factors not examined in this study. This research emphsizes the importance of improving service quallity to enhance customer satisfaction.